From Exile to a Global Citizen - Ahmed, Tahmina (Spectrum, 2023)
In ancient Greek literature and Indian epics, Mahabharata and Ramayana, exile or banishment is depicted as a punishment meted out for sins and crimes committed by humans, whether knowingly or unknowingly. Gradually, from individual/ group punishment, exile evolved into mass exodus resulting from war, conquests and other conflicts. All forms of exiles suffer from the pain and sorrow of leaving behind one’s homeland and belongings. Consequently, the literature produced by exiled poets and writers are filled with nostalgia and agonizing memories. However, over the years, other concerns related to their new lives gain prominence in their writings. This paper attempts to trace the journey of exiles from the past to the present and move towards the future in the writings of diasporic writers of different decades. This paper will focus on the works of V.S. Naipaul, Monica Ali, Zia Haider Rahman and Tarfia Faizullah to discover the newer trends emerging in their texts. V.S. Naipaul’s A House for Mr Biswas (1961) is the epitome of the diasporic writer’s attempt to understand his past in relation to his present. The ownership of a house in the new country is like staking a claim to belong to that country, and Mr. Biswas is desperate to do so. On the other hand, Monical Ali’s Brick Lane, published at the turn of the century, deals with a husband and wife negotiating the difficulties of belonging to a new society. Zia Haider Rahman and Tarfia Faizullah belong to the next group of diaspora writers, who are second generation immigrants growing up in a new land no longer ‘foreign’ to them. The protagonist of Rahman’s novel in The Light of What We Know (2014) successfully confronts problems and complications to ‘belong’ and ‘become’ a British citizen. Tarfia Faizullah, a young Bangladeshi-American poet, uses the history of the War of Independence of Bangladesh to align it with other similar universal discourse of genocide. It appears that figuratively, the exiled writer has now arrived at an acceptable point where s/he is flying out as a global citizen. This transformation of diasporic writers from the periphery to the centre as globally read figures has given rise to the concept of transnationalism. Spectrum, Volume 17, June 2022: 1-11